IMPLEMENTATION OF PERSONAL SELLING AS A MARKETING COMMUNICATION MIX FOR PESANTREN PRODUCTS: A Study at Darun Najah Islamic Boarding School and Al-Haromain Islamic Boarding School - M Zakaria Husni (Indonesian Journal of Islamic Communication, 2023)
Islamic business competition always presents a competitive rivalry. Today, besides business being carried out in established companies and start-ups, business is also carried out by Islamic institutions. With the existence of the business world in Islamic institutions, there will also be a combination of Islamic institutional marketing communication models and corporate marketing communications by incorporating the values of marketing communications. The focus of the study are 1.) How is the Implementation of Personal Selling as a Marketing Communication Mix in a Sales-Oriented Approach at Pesantren Darun Najah and Pesantren Al-Haromain? 2.) How is the Implementation of Personal Selling as a Marketing Communication Mix in a Customer-Oriented Approach at Pesantren Darun Najah and Pesantren Al-Haromain? This study uses a qualitative phenomenological approach, while data collection uses in-depth interviews, observation, and documentation. The informant data collection technique was carried out by purposive sampling. Data analysis used induction analysis method and interpretation in the study. The results showed that the sales and customer-oriented approaches at Pesantren Darun Najah and Pesantren Al-Haromain were carried out with presentations by salespeople explaining as best they could. Those are about product information and not lying by applying the values of the Prophet Muhammad in trading, such as being honest sales-oriented approach held at alumni meetings, local communities, and bazaar activities. The customer-oriented approach places the customer at the sales process's beginning, middle, and end. Islamic boarding schools do this by gathering alumni to research market needs with deliberations to find information on customer needs about products so that they can satisfy customers.